Low-dielectric non-flowing prepreg and application thereof
By introducing polyphenylene ether resin, bismaleimide resin and core-shell rubber premix solution into the resin composition, and combining cyclic polyolefin and glass fiber cloth, poor compatibility of resin compositions in the prior art is solved and The problem of dielectric performance deviation has achieved a low-flow adhesive semi-cured sheet material with high heat resistance and low dielectricity.
Patent Information
- Application Number
- CN202411536484.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, in order to reduce the flowability of the resin, the high polarity, low glass transition temperature and high molecular weight thermoplastic resin used with thermosetting epoxy resin leads to poor compatibility of the resin composition, dielectric properties deviation and glass transition temperature. Lower, reducing its heat resistance, dielectric properties and adhesion.
A curable resin composition including polyphenylene ether resin, bismaleimide resin and core-shell rubber premix, and a cyclic polyolefin, is adopted, and a glass fiber is combined with inorganic fillers, catalysts, initiators and flame retardants. As a reinforcement material, the cloth regulates the resin's rubber resistance and dielectric properties.
It realizes high heat resistance, low dielectricity, excellent processability and high bonding, which improves the dielectric properties and heat resistance of the resin and meets the high heat resistance and low dielectric requirements.
Smart Images

Figure BDA0005111672520000035 
Figure BDA0005111672520000046 
Figure BDA0005111672520000052
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic materials, and in particular to a low-dielectric no-flow prepreg and application thereof. Background Art
[0002] With the rapid development of consumer electronic products, the requirements of electronic products for circuit boards are getting higher and higher, and a special circuit board-rigid-flex board came into being. Rigid-flex board has the advantages of both rigid board and flexible board. It can not only weld complex electronic components on rigid board, but also has the characteristics of flexible board that it is thin, foldable, bendable, and takes up little space, effectively reducing the volume of electronic products. No-Flow Prepreg for Rigid-Flex Board is a special adhesive material used in the preparation process of Rigid-Flex Board to tightly connect the rigid board and the flexible board through a specific pressing process. No-Flow Prepreg for Rigid-Flex Board usually refers to a semi-cured solid film prepared by impregnating epoxy resin adhesive with glass fiber cloth as a carrier, and then semi-curing treatment. It is characterized by the resin not flowing or having very low fluidity, and having certain adhesive characteristics, which meets the process requirements of rigid-flex printed circuit boards.
[0003] In the prior art, in order to reduce the fluidity of the resin, a thermoplastic resin with high polarity, low glass transition temperature and high molecular weight is often used in combination with a thermosetting epoxy resin, resulting in poor compatibility of the resin composition, deviation in dielectric properties and a low glass transition temperature, thereby reducing its heat resistance, dielectric properties and adhesion.
[0004] Therefore, the present invention provides a low-dielectric no-flow prepreg and its application to realize a low-flow prepreg material having high heat resistance, low dielectric property, high adhesion and excellent processability. Summary of the invention
[0005] The object of the present invention is to provide a low-dielectric no-flow prepreg and application thereof, so as to realize a low-flow prepreg material having high heat resistance, low dielectric property, high adhesion and excellent processability.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A low-dielectric no-flow prepreg comprises: a curable resin insulating layer and a reinforcing material;
[0008] In parts by weight, the curable resin insulation layer is a curable resin composition layer, and the curable resin composition includes the following components:
[0009] (A) polyphenylene ether resin: 0-100 parts;
[0010] (B) bismaleimide resin: 0-100 parts;
[0011] (C) core-shell rubber premix: 10-50 parts;
[0012] (D) cyclic polyolefin: 5-40 parts;
[0013] The core-shell rubber premix is a mixed dispersion of epoxy resin, organic solvent and core-shell rubber, wherein the content of the core-shell rubber is 10%-50% by mass percentage.
[0014] Preferably, the content of the core-shell rubber in the core-shell rubber premix is 20%-40%.
[0015] For example, the content of the core-shell rubber in the core-shell rubber premix is 20%, 25%, 30%, 35% or 40%.
[0016] Preferably, the shell part of the core-shell rubber is selected from at least one of methacrylates, acrylates, and styrenes; the core part is selected from at least one of butadiene rubber, acrylate rubber, silicone rubber, NBR rubber, and SBR rubber.
[0017] Preferably, the average particle size of the core-shell rubber is 0.1 micrometer to 3 micrometers.
[0018] For example, the core-shell rubber premix is MX-217 manufactured by KANEKA.
[0019] Preferably, the organic solvent is selected from at least one of acetone, butanone, toluene, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane; further preferably, the organic solvent is toluene or xylene.
[0020] Preferably, the epoxy resin includes at least two epoxy groups in one molecular structure; the epoxy resin is selected from at least one of biphenyl epoxy resin, naphthalene epoxy resin, dicyclopentadiene epoxy resin, polyphenylene ether modified epoxy resin, and phosphorus-containing epoxy resin.
[0021] Further preferably, the epoxy resin is selected from at least one of the following structures:
[0022] Wherein, p is an integer from 1 to 20;
[0023] Wherein, n is an integer from 1 to 20;
[0024] Wherein, m is an integer from 0 to 20;
[0025] Wherein, n is an integer from 1 to 20;
[0026] Wherein, n is an integer from 1 to 20;
[0027]
[0028] Wherein, n is an integer of 1-20.
[0029] For example, the epoxy resin is selected from NC-3000, NC-2000, EPPN-500, NC-7000, NC-3500, XD-1000 manufactured by Nippon Kayaku; HP-4032SS, HP-4770, EXA-4750, HP-4700, HP-4710, HP-6000, HP-9500, HP-9540, HP-9900 or EXA-7311 manufactured by DIC.
[0030] Preferably, the polyphenylene ether resin is at least one selected from hydroxyl-modified polyphenylene ether resin, methacrylate-modified polyphenylene ether resin, styrene-modified polyphenylene ether resin, and allyl-modified polyphenylene ether resin.
[0031] More preferably, the number average molecular weight of the polyphenylene ether resin is 1000-3000.
[0032] More preferably, the polyphenylene ether resin is selected from one or more of the compounds represented by the following structural formulas (18), (19), and (20):
[0034] Wherein: X2 is selected from the following structures:
[0035] Among them, R1, R3, R6, R8, R9, R 11 , R 14 , R 16 , R 17 , R 19 , R 22 , R 24 are the same or different and are halogen atoms, alkyl groups or phenyl groups; wherein R2, R4, R5, R7, R 10 , R 12 , R 15 , R 18 , R 20 , R 21 , R 23 are the same or different and are respectively a hydrogen atom, a halogen atom, an alkyl group or a phenyl group;
[0036] The structure of -Y2-O- is: Where R 26 , R 28 are the same or different and are respectively a halogen atom, an alkyl group or a phenyl group, R 25 , R 27 are respectively a hydrogen atom, a halogen atom, an alkyl group or a phenyl group;
[0037] m and n represent integers from 0 to 30 respectively, and cannot be 0 at the same time;
[0038] Where n is an integer greater than 5;
[0039] The acrylate-modified polyphenylene ether resin is selected from one or more of the compounds represented by the following structural formula (20):
[0040]
[0041] Among them: Y3 is Wherein m and n are integers greater than or equal to 1 respectively.
[0042] For example, the polyphenylene ether resin is selected from SA90 and SA9000 manufactured by SABIC and OPE-2St manufactured by Mitsubishi Gas.
[0043] Preferably, the bismaleimide resin is selected from at least one of the following structures:
[0044] R is hydrogen, methyl or ethyl, and n is an integer from 1 to 10;
[0045]
[0046] R2 is hydrogen, methyl or ethyl, R1 is methylene or ethylene, and n is an integer from 1 to 10;
[0047]
[0048] n is an integer from 1 to 10;
[0049] n is an integer from 1 to 10;
[0050]
[0051] For example, BMI-1000, BMI-1100, BMI-2000, BMI-2300, BMI-3000, BMI-4000, BMI-5100, and BMI-7000 manufactured by Yamato of Japan are selected.
[0052] Preferably, the cyclic polyolefin is an unmodified cyclic polyolefin or a modified cyclic polyolefin.
[0053] The modified cyclic polyolefin is selected from at least one of epoxy-modified cyclic polyolefin, hydroxy-modified cyclic polyolefin, anhydride-modified cyclic polyolefin and ester-modified cyclic polyolefin.
[0054] More preferably, the cyclic polyolefin is a norbornene compound or a modified product thereof.
[0055] For example, TOPAS6013, TOPAS8007, TOPAS6015 or TOPAS5013 made by Polyplastics is selected.
[0056] Preferably, the curable resin insulation layer does not contain phenoloxy resin.
[0057] In the above technical solution, the curable resin insulating layer also includes inorganic fillers, and the content of inorganic fillers is 30-150 parts.
[0058] Preferably, the inorganic filler is selected from at least one of silicon dioxide, aluminum hydroxide, aluminum oxide, talc, aluminum nitride, boron nitride, silicon carbide, barium sulfate, boehmite, barium titanate, strontium titanate, calcium carbonate, calcium silicate, mica, and glass fiber powder.
[0059] More preferably, the inorganic filler is spherical silica that has been surface treated with an aniline silane coupling agent.
[0060] Preferably, the structural formula of the phenylaminosilane coupling agent is: Wherein, R is a C1-C6 straight chain alkylene group, and X is a methoxy group or an ethoxy group.
[0061] In the above technical solution, the curable resin insulation layer further comprises a catalyst, and the content of the catalyst is 0.01-5 parts by weight.
[0062] Preferably, the catalyst is selected from at least one of imidazole catalysts, pyridine catalysts and organic metal salt catalysts.
[0063] Further preferably, the catalyst is selected from at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole and zinc octoate.
[0064] In the above technical solution, the curable resin insulation layer further includes an initiator, and the content of the initiator is 0.01-5 parts by weight.
[0065] Preferably, the initiator is selected from at least one of an organic peroxide free radical initiator or an alkyl free radical initiator.
[0066] Preferably, the organic peroxide free radical initiator is selected from diisopropylbenzene peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, 2,5-di-tert-butylperoxy-2,5-dimethylhexane, tert-butylperoxide, or a combination of the two.
[0067] Preferably, the alkyl free radical initiator is selected from one or a combination of 2,3-dimethyl-2,3-diphenylbutane, 2,3-dimethyl-2,3-di(4-methylphenyl)butane, 2,3-dimethyl-2,3-di(4-isopropylphenyl)butane, and 3,4-dimethyl-3,4-diphenylhexane.
[0068] In the above technical solution, the curable resin insulation layer further comprises a flame retardant, the content of which is 5-50 parts by weight, and the flame retardant is a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant or a silicon flame retardant.
[0069] The brominated flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide.
[0070] The phosphorus flame retardant is selected from inorganic phosphorus, phosphate ester, phosphoric acid, hypophosphorous acid, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ), (m is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene or modified phosphazene.
[0071] Preferably, the reinforcing material is glass fiber cloth, and the glass fiber cloth is surface treated with a silane coupling agent.
[0072] Preferably, the glass fiber cloth is preferably open fiber cloth or flat cloth; more preferably, the glass fiber cloth is E glass fiber cloth, S glass fiber cloth or Q glass fiber cloth.
[0073] When the reinforcing material is glass fiber cloth, the glass fiber cloth is chemically treated with a coupling agent in advance to improve the interface bonding between the resin composition and the glass fiber cloth. The coupling agent here is preferably an epoxy silane coupling agent or an amino silane coupling agent to provide good water resistance and heat resistance.
[0074] The present application also claims to protect the use of the above-mentioned low-dielectric no-flow prepreg in a rigid-flexible printed circuit board.
[0075] The specific preparation method of the above-mentioned semi-cured sheet is as follows: add the resin composition into a mixing kettle, add a diluent to adjust the solid content to 40-70%, stir evenly to form a glue solution, immerse the reinforcing material in the glue solution, and then bake the impregnated reinforcing material at 100-200°C for 3-10 minutes to obtain the low-flow semi-cured sheet provided by the present invention.
[0076] Due to the application of the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0077] The present invention combines polyphenylene ether resin, bismaleimide resin, core-shell rubber premix and cyclic polyolefin, wherein the cyclic polyolefin is introduced to adjust the adhesive resistance and greatly improve the dielectric properties, thereby obtaining a resin composition with excellent low dielectric, heat resistance, non-flowability and low water absorption, which is used in the field of non-flowable semi-cured sheets with high heat resistance and low dielectric requirements. DETAILED DESCRIPTION
[0078] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.
[0079] The present invention is further described below in conjunction with the examples, but the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0080] Example 1
[0081] This embodiment is a curable resin composition, which includes, by weight: 60 parts of polyphenylene ether resin, 60 parts of bismaleimide resin, 20 parts of core-shell rubber premix, 20 parts of cyclic polyolefin, 40 parts of spherical silica, and 0.1 parts of dimethylimidazole.
[0082] Example 2
[0083] This embodiment is a curable resin composition, which includes, by weight: 80 parts of polyphenylene ether resin, 40 parts of bismaleimide resin, 20 parts of core-shell rubber premix, 20 parts of cyclic polyolefin, 40 parts of spherical silica, and 0.1 parts of dimethylimidazole.
[0084] Example 3
[0085] The present embodiment is a curable resin composition, which includes, by weight: 60 parts of polyphenylene ether resin, 60 parts of bismaleimide resin, 40 parts of core-shell rubber premix, 20 parts of cyclic polyolefin, 40 parts of spherical silica, and 0.1 parts of dimethylimidazole.
[0086] Example 4
[0087] The present embodiment is a curable resin composition, which includes, by weight: 60 parts of polyphenylene ether resin, 60 parts of bismaleimide resin, 20 parts of core-shell rubber premix, 40 parts of cyclic polyolefin, 40 parts of spherical silica, and 0.1 parts of dimethylimidazole.
[0088] Comparative Example 1
[0089] This embodiment is a curable resin composition, which includes, by weight: 60 parts of polyphenylene ether resin, 60 parts of bismaleimide resin, 40 parts of cyclic polyolefin, 40 parts of spherical silica, and 0.1 parts of dimethylimidazole.
[0090] Comparative Example 2
[0091] This embodiment is a curable resin composition, which includes, by weight: 60 parts of polyphenylene ether resin, 60 parts of bismaleimide resin, 40 parts of core-shell rubber premix, 40 parts of spherical silica, and 0.1 parts of dimethylimidazole.
[0092] Comparative Example 3
[0093] This embodiment is a curable resin composition, which includes, by weight: 60 parts of polyphenylene ether resin, 60 parts of bismaleimide resin, 40 parts of phenoloxy resin, 40 parts of spherical silica, and 0.1 parts of dimethylimidazole.
[0094] Comparative Example 4
[0095] This embodiment is a curable resin composition, which includes, by weight: 60 parts of polyphenylene ether resin, 60 parts of bismaleimide resin, 20 parts of core-shell rubber, 20 parts of cyclic polyolefin, 40 parts of spherical silica, and 0.1 parts of dimethylimidazole.
[0096] The components and addition amounts of Examples 1-4 and Comparative Examples 1-4 are shown in Table 1 below.
[0097] Table 1
[0098] Components Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Polyphenylene ether resin 60 80 60 60 60 60 60 60 Bismaleimide resin 60 40 60 60 60 60 60 60 Core-shell rubber premix 20 20 40 20 0 40 0 0 Cyclic polyolefins 20 20 20 40 40 0 0 20 Phenoloxy resin 0 0 0 0 0 0 40 0 Core-shell rubber 0 0 0 0 0 0 0 20 Spherical silica 40 40 40 40 40 40 40 40 dimethylimidazole 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1
[0099] The raw material manufacturers and models of each component used in Examples 1-4 and Comparative Examples 1-4 are shown in Table 2 below.
[0100] Table 2
[0101] Components Brand Polyphenylene ether resin SABIC, SA90 Bismaleimide resin Yamato, Japan, BMI-1000 Core-shell rubber premix Kaneka, MX217 Core-shell rubber Made by Dow, PraraloidTMS-2670J Cyclic polyolefins Polyplastics, TOPAS6013 Phenoloxy resin Nippon Steel, YP-50 Spherical silica Lianrui New Materials, D100=13um
[0102] The above-mentioned embodiments and comparative examples also disclose a prepreg, comprising glass fiber cloth as a reinforcing material and a resin composition coated on the glass fiber cloth by an impregnation method; wherein the glass fiber cloth is a fiber-spreading cloth pre-treated with an epoxy silane coupling agent.
[0103] Specifically, the components of the resin compositions of the above-mentioned Examples 1-4 and Comparative Examples 1-4 were dissolved in toluene, stirred and mixed, and then diluted into a glue solution with a solid content of 60wt%; the E glass fiber cloth 1078 used as a reinforcing material was pretreated with an epoxy silane coupling agent, immersed in the above-mentioned glue solution, taken out after infiltration, placed in a 180°C blast drying oven, and baked for 5-8 minutes to obtain a semi-cured sheet.
[0104] The above embodiment and comparative example also disclose a laminate, which is prepared by the following method:
[0105] Take two of the above-mentioned semi-cured sheets, cut them to 300×300mm, and stack them into a composite sheet with a certain stacking structure. Then, place a low-profile electrolytic copper foil with a thickness of 12 microns on both sides of the composite sheet, place it in a vacuum hot press, and hot press it for 3 hours at a pressure of 1.5 MPa and a temperature of 220°C to obtain a copper-clad laminate.
[0106] The above-mentioned embodiments and comparative examples also disclose an insulating board, comprising at least one of the above-mentioned prepreg sheets.
[0107] The above embodiments and comparative examples also disclose an insulating film, including a carrier film and the above resin composition coated thereon.
[0108] The above-mentioned embodiment and comparative example also disclose a circuit substrate, including a prepreg sheet mentioned above, which is prepared by a conventional preparation method in the prior art, and will not be described in detail here.
[0109] The performance tests were conducted on the prepregs obtained in the above Examples 1-4 and Comparative Examples 1-4 and the copper-clad laminates pressed therefrom, respectively. The test results are shown in Table 3 below.
[0110] Table 3
[0111]
[0112] The properties of the copper-clad laminates prepared in the above examples and comparative examples were tested as follows:
[0113] (1) Glue overflow: measured according to IPC-TM650, 2.3.17.2 method;
[0114] (2) CVL adhesion: Sample width 10 mm, tested using a peel force tester;
[0115] (3) Powder loss rate: The prepreg sheet is 10 cm × 10 cm in size. Use a utility knife to score 20 times before calculating the weight loss.
[0116] (4) Tg: DMA, heating rate 10°C / min, frequency 10 Hz;
[0117] (5) Dk and Df: Dielectric properties at 10 GHz using the flat plate method in accordance with IPC-TM-650, 2.5.5.9;
[0118] (6) Peel strength: According to the "after thermal stress" experimental conditions in IPC-TM-650, method 2.4.8, the peel strength of the metal cover layer was tested;
[0119] (7) Internal substrate quality: The internal substrate quality was observed under a microscope. When there was no resin agglomeration within an area of 300 mm × 300 mm, it was indicated as 0. When there was resin agglomeration, it was indicated as ╳.
[0120] In summary, the present invention combines polyphenylene ether resin, bismaleimide resin, core-shell rubber premix and cyclic polyolefin, wherein the cyclic polyolefin is introduced to adjust the adhesive resistance and greatly improve the dielectric properties, thereby obtaining a resin composition with excellent low dielectric, heat resistance, non-flowability and low water absorption, which is used in the field of non-flowable semi-cured sheets with high heat resistance and low dielectric requirements.
[0121] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A low dielectric no-flow prepreg, characterized in that: include: Curable resin insulation layer and reinforcement material; In parts by weight, the curable resin insulation layer is a curable resin composition layer, and the curable resin composition includes the following components: (A) polyphenylene ether resin: 0-100 parts; (B) bismaleimide resin: 0-100 parts; (C) core-shell rubber premix: 10-50 parts; (D) cyclic polyolefin: 5-40 parts; The core-shell rubber premix is a mixed dispersion of epoxy resin, organic solvent and core-shell rubber, wherein the content of the core-shell rubber is 10%-50% by mass percentage.
2. The low dielectric no-flow prepreg according to claim 1, characterized in that: The epoxy resin is selected from at least one of the following structures: Wherein, p is an integer from 1 to 20; Wherein, n is an integer from 1 to 20; Wherein, m is an integer from 0 to 20; Wherein, n is an integer from 1 to 20; Wherein, n is an integer from 1 to 20; Wherein, n is an integer of 1-20.
3. The low dielectric no-flow prepreg according to claim 1, characterized in that: The polyphenylene ether resin is selected from at least one of hydroxyl-modified polyphenylene ether resin, methacrylate-modified polyphenylene ether resin, styrene-modified polyphenylene ether resin and allyl-modified polyphenylene ether resin.
4. The low dielectric no-flow prepreg according to claim 3, characterized in that: The number average molecular weight of the polyphenylene ether resin is 1000-10000.
5. The low dielectric no-flow prepreg according to claim 1, characterized in that: The bismaleimide resin is selected from at least one of the following structures: R is hydrogen, methyl or ethyl, and n is an integer from 1 to 10; R2 is hydrogen, methyl or ethyl, R1 is methylene or ethylene, and n is an integer from 1 to 10; n is an integer from 1 to 10; n is an integer from 1 to 10; 6. The low dielectric no-flow prepreg according to claim 1, characterized in that: The shell part of the core-shell rubber is selected from at least one of methacrylates, acrylates and styrenes; the core part is selected from at least one of butadiene rubber, acrylate rubber, silicone rubber, NBR rubber and SBR rubber.
7. The low dielectric no-flow prepreg according to claim 1, characterized in that: The organic solvent is selected from at least one of acetone, butanone, toluene, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene and cyclohexane.
8. The low dielectric no-flow prepreg according to claim 1, characterized in that: The curable resin insulating layer does not contain phenoloxy resin.
9. The low dielectric no-flow prepreg according to claim 1, characterized in that: The curable resin insulating layer further comprises a catalyst, the content of which is 0.01-5 parts; the catalyst is selected from at least one of imidazole catalysts, pyridine catalysts and organic metal salt catalysts.
10. An application of a low dielectric no-flow prepreg, characterized in that: Application of the low dielectric no-flow prepreg described in any one of claims 1 to 9 in a rigid-flexible printed circuit board.
Citation Information
Cited By
Resin composition and application thereof
CN121427279A